167k views
2 votes
-(4x-3)=3x-4 * would it be 1 2 3

1 One Solution; x=1
2 No Solution
3 Infinite Solutions

User Nashawn
by
4.7k points

2 Answers

6 votes
The answer is 1. One solution; x=1
User Matt Warrick
by
5.1k points
4 votes

Answer:

1

Explanation:

Step 1:

- ( 4x - 3 ) = 3x - 4 Equation

Step 2:

- 4x + 3 = 3x - 4 Open Parenthises

Step 3:

3 = 7x - 4 Add 4x on both sides

Step 4:

7 = 7x Add 4 on both sides

Answer:

x = 1 Divide

Hope This Helps :)

User Lazar Kukolj
by
4.9k points